Meningkatkan Mutu Pengelolaan Madrasah Untuk Meningkatkan Minat Masyarakat - Wenni, Wenni; Rivauzi, Ahmad (YASIN, 2023)
This research was motivated by the lack of public interest in sending their children to Madrasah Diniyah Takmiliyah, which triggered researchers to be moved to conduct this research with the aim of this study to find out the factors that caused the lack of interest in the community to send their children to Madrasah Diniyah Takmiliyah Awaliyah Muhammadiyah. This type of research is field research and the method used is qualitative research methods. The results of the research are what researchers do regarding the factors that cause a lack of public interest in sending their children to Madrasah Diniyah Takmiliyah Awaliyah Muhammadiyah, which is caused by two factors, internal and external factors. Internal factors are factors that come from the child himself such as (nature, habits, intelligence, physical and psychological conditions), while external factors such as (teachers, learning environment, facilities and infrastructure, and parents).